The Influence of Financial Literacy and Financial Behavior on Financial Management Employee Survey of PT. Spirit Jaya Snack & Coffee - Benikna Maria Ines Liti; Elly Lestari; Anung Prasetyo Nugroho (International Research & Development for Human Beings (IRDH), 2025)
Financial management is an increasingly important skill for individuals and businesses in the era of globalization and rapid economic expansion. Good financial management has a major impact on the financial health of workers, which in turn affects their productivity in the workplace. This study examines how employee financial management at PT. Spirit Jaya Snack and Coffee is influenced by behavior and financial literacy. A questionnaire filled out by 43 respondents was used to collect data, and SPSS was used for multiple regression analysis. Based on the findings, Financial management skills are becoming increasingly important for individuals and organizations in this era of rapid economic expansion and globalization. An employee's financial well-being and, ultimately, their productivity at work will be greatly affected by their capacity to manage money. The findings of the study show that financial literacy has a greater influence on employee financial management than financial behavior. The suggestion from this research for the nexr research is exploring whether factors like age, education level, or job position moderate the relationship between financial literacy and management practices